Toward a Sustainable Editorial Ecosystem: General Diagnosis and Management Proposal - Endara Rosales, Sebastián (Revista del Hospital Italiano de Buenos Aires, 2026)
This work reflects on the university publishing system within the framework of the transformations imposed by the so-called academic capitalism, characterized by the pressure to meet indicators, reputational competition, and the standardization of scientific production. From a critical perspective, it develops a conceptual framework that makes it possible to understand how these dynamics shape certain editorial practices and condition the capacity of universities to sustain socially meaningful publication projects. Based on this analytical foundation, the study proposes renewed criteria and functions for academic publishing, managed through an institutionally articulated model that embraces epistemic plurality and is committed to decolonizing perspectives. The research draws on the experience of reconstructing the publishing system at the Catholic University of Cuenca, which serves as a case study to demonstrate the applicability of the proposed guidelines. The result is an approach that offers tools for rethinking university editorial management from an integrative, ethical, and public-oriented perspective. The work contributes to broadening the discussion on the role of scientific publications in the contemporary landscape and to outlining pathways for their institutional transformation.
Keywords: academic publishing; editorial policy; social transformation; academic capitalism